A mixed methods quality improvement study to implement nurse practitioner roles and improve care for residents in long-term care facilities - Kelley Kilpatrick; Éric Tchouaket; Mira Jabbour; Sylvie Hains (BMC, 2020)
Abstract Background To better meet long-term care (LTC) residents' (patients in LTC) needs, nurse practitioners (NPs) were proposed as part of a quality improvement initiative. No research has been conducted in LTC in Québec Canada, where NP roles are new. We collected provider interviews, field notes and resident outcomes to identify how NPs in LTC influence care quality and inform the wider implementation of these roles in Québec. This paper reports on resident outcomes and field notes. Methods Research Design: This mixed methods quality improvement study included a prospective cohort study in six LTC facilities in Québec. Participants: Data were collected from September 2015-August 2016. The cohort consisted of all residents (n = 538) followed by the nurse practitioners. Nurse practitioner interventions (n = 3798) related to medications, polypharmacy, falls, restraint use, transfers to acute care and pressure ulcers were monitored. Analysis: Bivariate analyses and survival analysis of occurrence of events over time were conducted. Content analysis was used for the qualitative data. Results Nurse practitioners (n = 6) worked half-time in LTC with an average caseload ranging from 42 to 80 residents. Sites developed either a shared care or a consultative model. The average age of residents was 82, and two thirds were women. The most common diagnosis on admission was dementia (62%, n = 331). The number of interventions/resident (range: 2.2-16.3) depended on the care model. The average number of medications/resident decreased by 12% overall or 10% for each 30-day period over 12 months. The incidence of polypharmacy, falls, restraint use, and transfers to acute care decreased, and very few pressure ulcers were identified. Conclusions The implementation of NPs in LTC in Québec can improve care quality for residents. Results show that the average number of medications per day per resident, the incidence of polypharmacy, falls, restraint use, and transfers to acute care all decreased during the study, suggesting that a wider implementation of NP roles in LTC is a useful strategy to improve resident care. Although additional studies are needed, the implementation of a consultative model should be favoured as our project provides preliminary evidence of the contributions of these new roles in LTC in Québec.